GAMBARAN PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) DI RUMAH SAKIT TENTARA TK III Dr. REKSODIWIRYO PADANG - Danhas, Yunhendri; Prihartono, Agus Teguh (Ensiklopedia of Journal, 2023)
Along with the increase in the number of hospitals in Indonesia, the potential for an increase in hospital waste will increase also. One type of waste that has the potential to pollute the environment and adversely affect human health is B3 waste. The aims of this study were (1) to find out the description of the B3 waste sorting at the Tk III Army Hospital, dr. Reksodiwiryo Padang, (2) what is the description of B3 waste storage at the TNI Hospital III dr. Reksodiwiryo Padang and (3) to find out the description of the transport of B3 waste at the TNI Hospital III dr. Reksodiwiryo Padang. The research method is descriptive qualitative using data validation techniques through data triangulation. The results of the study show that the management of infectious B3 waste carried out at Dr. Reksodiwiryo Hospital complies with the requirements listed in the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.56 of 2015 starting from the segregation of B3 waste, the storage of B3 waste, the transportation of B3 waste. It is recommended (1) RST dr. Reksodiwiryo Tk III Padang is expected to be able to socialize medical staff and visitors to the hospital to dispose of garbage in accordance with the containers provided, (2) for containers for sharps waste, an additional number of safety boxes is added to avoid the use of ordinary cardboard/jerry cans, (3) if emptying of the TPS cannot be carried out within 48 hours, it is necessary to install a cooling device in the TPS room to prevent waste decomposition and gas formation.